(untitled) (Research, Society and Development, 2022)
Introduction: The COVID-19 pandemic demanded new ways of acting from health systems. Telemonitoring emerges as a possibility of safe access to patients, enabling remote assistance and surveillance of cases. Objective: describes the difficulties, limitations, facilities and potentialities experienced by health professionals using ICTs to monitor cases of COVID-19 in the city of Una, Bahia, Brazil. Method: This is an evaluative study, having as a research strategy the single case study, involving health professionals who acted in the fight against the pandemic, both in PHC and in Health Surveillance, between 2020 and 2021. Triangulation was used for data analysis, in addition to a matrix to assess the degree of incorporation of telemonitoring. The content analysis of the interviews made it possible to organize them into cores of meaning, articulated to the components of the matrix. Results: The sample consisted of 14 professionals (85.71% nurses), aged between 23-51 years old, 35 years old in average. Of these, 28.57% worked in health surveillance and 71.43% in PHC. The telemonitoring of COVID-19 was considered incorporated, and the degrees of adequacy were reached for the components: municipal organization (72.29%), epidemiological surveillance (72.67%), case assistance (77.00%), education in health (44.67%). Low digital coverage, unavailability of institutional telephone and insufficient training were some of the obstacles identified. Use of ICTs and the involvement of professionals with human life emerged as facilities. Conclusion: The incorporation of telemonitoring enabled safe and timely care. The study reinforces the importance of continuing education in health to qualify the care network.